2020
DOI: 10.1136/bjophthalmol-2019-315298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopic macular degeneration worldwide: a systematic review and meta-analysis

Abstract: PurposeTo investigate the prevalence of myopic macular degeneration (MMD) in the global population.MethodsAll published literature of population-based studies on MMD prevalence worldwide were searched and only those with clear definitions to diagnose and classify MMD lesions by standardised grading methods were selected. Meta-analysis methods were used to calculate the pooled prevalence of MMD and its 95% CI in a random-effects model. The prevalence of MMD lesions would also be reported, together with the subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
0
28
1
1
Order By: Relevance
“…Recently, a meta‐analysis revealed that females had a higher risk of myopic macular degeneration than males (Zou et al. 2020). However, its internal mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a meta‐analysis revealed that females had a higher risk of myopic macular degeneration than males (Zou et al. 2020). However, its internal mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The female sex has also been reported to increase the risk of myopic maculopathy progression (Fang et al 2018). Recently, a metaanalysis revealed that females had a higher risk of myopic macular degeneration than males (Zou et al 2020). However, its internal mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Of these, myopic retinopathy or MMD is fast emerging as one of the leading causes of blindness in East Asia and else-where. 15,17,40 A recent meta-analysis found a pooled prevalence of MMD in the world population of 2.1% (increasing from 1.3% in the 40-49 age group to 4.5% in the 70+ age group) 41 and found a higher frequency of MMD from data reported from 2007 to 2019 compared to 1993 to 2006. Vision impairment from MMD was estimated to have affected 10 million people (0.13% of world's population) in 2015 and, if the trajectory for the rising prevalence of myopia and high myopia continues at the same pace, it is set to grow to nearly 56 million (0.6%) by the year 2050.…”
Section: Life-course Of Myopiamentioning
confidence: 99%
“…Amid the different conditions that can deteriorate the status of the macula, two are the conditions that appear more often: the myopic macular degeneration, which occurs in the presence of high myopia [1], and the age-related macular degeneration (AMD), which usually appears in the last decades of life [2]. Myopic macular degeneration and AMD combined affect approximately 11% of the world's population [1,3].…”
Section: Introductionmentioning
confidence: 99%